Detection and alterations of acetylcarnitine in human skeletal muscles by 1H MRS at 7 T - Klepochová, R; Valkovič, L; Gajdošík, M; Hochwartner, T; Tschan, H; Krebs, M; Trattnig, S; Krššák, M (Lippincott, Williams & Wilkins, 2017)
Objectives The aims of this study were to detect the acetylcarnitine resonance line at 2.13 ppm in the human vastus lateralis and soleus muscles, assess T1 and T2 relaxation times, and investigate the diurnal and exercise-related changes in absolute concentration noninvasively, using proton magnetic resonance spectroscopy at 7 T.